2005
DOI: 10.1523/jneurosci.2544-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxy-3-Methylglutaryl-Coenzyme A Reductase Inhibitors Attenuate β-Amyloid-Induced Microglial Inflammatory Responses

Abstract: Alzheimer's disease (AD) is characterized by extracellular deposits of fibrillar ␤-amyloid (A␤) in the brain, a fulminant microglialmediated inflammatory reaction, and neuronal death. The use of 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors (statins) is associated with a reduced risk of AD, which has been attributed to the cholesterol-lowering actions of these drugs. Statins have been reported recently to have anti-inflammatory actions in addition to their classic lipid-lowering effects. We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 78 publications
2
109
0
3
Order By: Relevance
“…The proposed mechanisms by which statins may act include a reduction in brain Aβ production through alterations in metabolism of amyloid precursor protein [46] and a reduction in inflammation attributable to microglia activation [45] . In vitro experiments have shown that statins attenuate inflammatory responses mediated by Aβ peptides [47] . In vivo statin use has also resulted in robust anti-inflammatory effects [48] .…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanisms by which statins may act include a reduction in brain Aβ production through alterations in metabolism of amyloid precursor protein [46] and a reduction in inflammation attributable to microglia activation [45] . In vitro experiments have shown that statins attenuate inflammatory responses mediated by Aβ peptides [47] . In vivo statin use has also resulted in robust anti-inflammatory effects [48] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our laboratory and that of others have reported that neuroprotective efficacies of statins are mediated by their anti-inflammatory activity under various neurological disease conditions such as human multiple sclerosis [38] and its animal models [20,23,[33][34][35], Spinal cord injury [24], X-linked adrenoleukodystrophy [22], Alzheimer's disease [6], traumatic brain injury [39], and stroke [12]. In these studies, statins inhibited inflammatory signal cascades and gene expression through inhibition of isoprenylation of small GTPase (Ras and RhoA) [21,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…38 Statins have been shown to reduce the production of iNOS from activated microglial cells and macrophages. 39,40 Additionally, lovastatin was also shown to signifi cantly reduce prostaglandin E2 release from microglia, either under basal conditions or after stimulation by IL-1B, in primary cultures of rat cortical microglia. 41 Statins have also been shown in rats and human microglia to reduce the production of the proinfl ammatory cytokine IL-6.…”
Section: Effects Of Statins and Clinical Outcomesmentioning
confidence: 95%